How Do Bees Make Honey - Anna Claybourne (U.S.A Edc Pub, 1995)
-- Introduces young children to fundamental aspects of nature, science and technology-- Inspired by the questions children ask about the world around them-- Simple text and detailed illustrations answer questions in clear, step-by-step stages